2012
DOI: 10.1016/j.ijantimicag.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Augmented renal clearance in septic patients and implications for vancomycin optimisation

Abstract: a b s t r a c tThe aim of this study was to evaluate the effect of augmented renal clearance (ARC) on vancomycin serum concentrations in critically ill patients. This prospective, single-centre, observational, cohort study included 93 consecutive, critically ill septic patients who started treatment that included vancomycin by continuous infusion, admitted over a 2-year period (March 2006 to February 2008. ARC was defined as 24-h creatinine clearance (CL Cr ) > 130 mL/min/1.73 m 2 . Two groups were analysed: G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(143 citation statements)
references
References 19 publications
6
137
0
Order By: Relevance
“…In our study, logarithmic regression was adopted to estimate the correlation between steady-state trough concentration and CL cr , which was better than the linear regression reported by the previous literatures (Baptista et al 2012;Minkut_ e et al 2013). Furthermore, a recent study in critically ill patients with ARC and administration by continuous infusion showed that vancomycin plasma clearance was correlated significantly with the 8-hour CL cr (Baptista et al 2014).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In our study, logarithmic regression was adopted to estimate the correlation between steady-state trough concentration and CL cr , which was better than the linear regression reported by the previous literatures (Baptista et al 2012;Minkut_ e et al 2013). Furthermore, a recent study in critically ill patients with ARC and administration by continuous infusion showed that vancomycin plasma clearance was correlated significantly with the 8-hour CL cr (Baptista et al 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, a phenomenon 'augmented renal clearance' (ARC) referring to enhanced renal elimination of circulating solutes has received increasing attention. It exerts a hypermetabolic status, which may increase renal blood flow and glomerular filtration (Udy et al 2010a(Udy et al , 2011aBaptista et al 2012;Minkut_ e et al 2013). It has also been reported that some patients with normal serum creatinine concentration might display elevated glomerular filtration rates (Udy et al 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, bias appeared to be greatest in emergent surgical and trauma admissions (Table 7.2), sub-groups where ARC has been previously well documented (84,88 (199,225), and clinical (104) implications. Unfortunately no readily accessible, pragmatic, error free measure of GFR is currently available.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, all of these factors lead to increased renal CL of some drugs, a phenomenon referred to as augmented renal clearance (ARC, defined as a creatinine clearance [CLCR] >130 mL/min). As hydrophilic antibiotics are predominantly cleared by the kidney, ARC in critically ill patients usually causes lower plasma concentrations [116][117][118][119][120][121][122][123][124].…”
Section: Increase In Cardiac Output and Augmented Renal Clearancementioning
confidence: 99%